Key Predictors for Reducing Chemotherapy-Induced Nausea and Vomiting Among Cancer Patients - Sari, Ike Wuri Winahyu; Rukmi, Dwi Kartika; Yulaikhah, Lily (http://dharmais.co.id/, 2025)
Background: Chemotherapy-induced nausea and vomiting (CINV) is a common and distressing side effect for many cancer patients. Given its high prevalence, it is essential to investigate additional factors associated with CINV. This study aimed to identify key predictors for reducing CINV in cancer patients undergoing chemotherapy.Method: This study used a descriptive-analytical design with a cross-sectional approach conducted in one of the public hospitals in Yogyakarta from March to September 2023. Of the 100 samples purposively selected, they joined the study. Inclusion criteria were patients with any cancer type undergoing chemotherapy, aged 18 years or older, and who had signed informed consent. Exclusion criteria included patients experiencing sudden emergencies or families not consenting to data collection. Demographic characteristics and CINV moments were measured during chemotherapy sessions using the Index of Nausea, Vomiting, and Retching (INVR), which measures experiencing symptoms over the previous 12 hours. The collected data were then analyzed using descriptive statistics. The correlation between demographic characteristics and CINV was analyzed using bivariate and multivariate analyses to identify the predictors of CINV.Results: The average INVR score among patients experiencing CINV was 9.20 ± 7.29, with a range of 0–32, and most patients experienced moderate CINV. Bivariate analysis revealed that cancer stage and the type of family caregiver were significantly correlated with CINV (both with p 0.001). Multivariate analysis confirmed that cancer stage (β = 0.440; p 0.001) and family caregiver type (β = 0.255; p = 0.004) were strong predictors of CINV. Patients in advanced cancer stages and those cared for by child caregivers were at higher risk for more severe CINV symptoms.Conclusion: The findings highlight key factors associated with CINV among cancer patients. Understanding these predictors can help in developing targeted interventions to manage CINV better. Educating patients and their families about CINV management and incorporating patient feedback into care practices could improve patient outcomes and overall well-being.